Die Wirtschaftspolitik des Dritten Reiches im besetzten Polen [The economic policy of the Third Reich in occupied Poland] - Łuczak, Czesław (Studia Historiae Oeconomicae, 1979)
Before the outbreak of war, the Hitler government had no precise economic policy plan for the Polish territories that were to be annexed. From the general statements of Hitler and Göring, which contained the most important principles of economic policy, it was clear that the Reich would not have to fear a blockade in the event of war, since the East would supply it with food, raw materials and the necessary workers. These principles therefore did not go beyond the scope of the economic policy that Prussia implemented in the Polish territories that had already been incorporated before World War I. These territories were suppliers of food and cheap labor for the highly industrialized regions of Germany. These general formulations of the goals of economic policy in occupied Poland before September 1, 1939, were subject to extensive crystallization in the first months of the war. Only from this point onwards can one speak of a fascist economic policy in the occupied territories of Poland, which was characterized by great stability with regard to the so-called eastern territories incorporated into the Reich, as well as by changes in its conception compared to the General Government.